Utilisations et représentations spatio-temporelles du numérique par des enseignants du secondaire - Xavière Lanéelle (Centre National d'Enseignement à Distance, 2017)
The spatio-temporal representations of the ICT are full of platitudes - whatever they are - and affect the uses. A qualitative survey led with teachers of high school in France had for object to spot these representations in their speeches.Teachers, members of the recent generations, think that they are more skillful with the ICT and consequently commit to it without reluctance. Others think that not being "digital natives" they will be limited in their practices. Nevertheless, it is not the case for all. Throughout their professional development, differentiated times of appropriation chant the uses. Besides the motivation for pedagogies and instrumented didactics - accelerating or not the appropriation of tools - the training was able to play its role. Furthermore, the representation of rhythms and growing intrusion of digital technology in private time can also explain the lack of enthusiasm of some.